A new species of Chudania Distant (Hemiptera: Cicadellidae: Nirvaninae) from China - Dai, Wu; Zhang, Yalin L. (Zootaxa, 2005)
In the present paper, a new species, Chudania guangxiana sp. nov., is described from China. A detailed morphological description and illustrations of the new species are provided. The type specimen is deposited in the Institute of Zoology, Chinese Academy of Sciences.